Bloodmeal host identities among sympatric Glossina austeni and Glossina pallidipes tsetse flies in Shimba Hills National Reserve, Kwale, Kenya - Ogolla, Kennedy O.; Onyango, Tevin; Bwana, Billiah K.; Otiende, Moses Y.; Mang’era, Clarence M.; Ochieng, Benard; Omolo, Maurice O.; Mugambi, John M.; Hassanali, Ahmed; Omondi, Patrick; Mireji, Paul O. (Frontiers in Tropical Diseases, 2023)
Odor from preferred/non-preferred tsetse fly vertebrate hosts have been exploited in R&D of attractants/repellents of the fly for human and livestock protection. Odors from vertebrate hosts of Glossina austeni and Glossina pallidipes tsetse flies can facilitate formulation of novel attractants effective against G. austeni or improvement of existing attractant blends for G. pallidipes. We compared vertebrate blood meal sources of both fly species at Shimba Hills National Reserve, Kenya, to establish putative preferred host of either species, hence potential source of G. austeni or G. pallidipes specific odors. We trapped sympatric adult flies in 2021 and 2022 using NGU traps/sticky panels baited with 3-propylphenol, octenol, p-cresol, and acetone (POCA), collected their blood meals and characterized the meals using High Resolution Melting (HRM) vertebrate 16S rRNA- PCR (for host identification), and compared host profiles using GLM and Fisher’s exact tests. We collected 168 and 62 sympatric G. pallidipes and G. austeni with bloodmeal, respectively in 2021 and, 230 and 142 respectively in 2022. In 2021, we identified putative hosts of 65.48 and 69.35% of the G. pallidipes and G. austeni respectively and 82.61 and 80.28%, respectively in 2022. In 2021, we detected harnessed bushbuck, buffalo, common warthog and cattle putative host bloodmeals, and additionally bushpig and suni antelope bloodmeals in 2022. Putative vertebrate bloodmeal sources were significantly different by tsetse fly species (χ²(1, N=457) = 43.215, p < 0.001) and sampling year (χ²(1, N=457) = 8.044, p = 0.005). Frequency of common warthog bloodmeals was higher in G. pallidipes (65.79%) than in G. austeni (38.60%), and that of suni antelope and harnessed bushbuck putative bloodmeals higher in G. austeni (21.05-28.07%) than in G. pallidipes (6.84 - 17.37%) in 2022. There was an apparent change in putative feeding preference/host choices in both fly species between 2021 and 2022. Host bloodmeals in G. pallidipes or G. austeni predominantly from putative harnessed bushbuck, suni antelope or common warthog reveal that these vertebrates have potential odors that can be harnessed and formulated into appropriate attractants for respective species and integrated into routine control regiment for G. pallidipes and/or G. austeni.